2020
DOI: 10.1039/c9ra10480a
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective colorimetric determination of catechol based on the aggregation-induced oxidase–mimic activity decrease of δ-MnO2

Abstract: A new determination mechanism for catechol: aggregation-induced oxidase-mimic activity decrease of δ-MnO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The sensitivity of both fluorescence and electrochemical sensor [29][30][31][32][33] are higher than that of the proposed colorimetric sensing platform for catechol determination due to the high sensitivity of the instruments themselves. However, compared with other nanozyme-based colorimetric sensing methods, [34][35][36] our method has higher sensitivity which is due to the fact that Ce 3+ /Ce 4+ redox electron pair transfer in PAA-CeO 2 makes it have strong laccase-like catalytic activity, and PAA-CeO 2 with laccase-like activity can directly catalyze the oxidation of catechol without adding additional oxidants. The result showed that the PAA-CeO 2 based colorimetric platform had acceptable sensitivity and linear range for the catechol determination.…”
Section: Determination Of Catecholmentioning
confidence: 97%
“…The sensitivity of both fluorescence and electrochemical sensor [29][30][31][32][33] are higher than that of the proposed colorimetric sensing platform for catechol determination due to the high sensitivity of the instruments themselves. However, compared with other nanozyme-based colorimetric sensing methods, [34][35][36] our method has higher sensitivity which is due to the fact that Ce 3+ /Ce 4+ redox electron pair transfer in PAA-CeO 2 makes it have strong laccase-like catalytic activity, and PAA-CeO 2 with laccase-like activity can directly catalyze the oxidation of catechol without adding additional oxidants. The result showed that the PAA-CeO 2 based colorimetric platform had acceptable sensitivity and linear range for the catechol determination.…”
Section: Determination Of Catecholmentioning
confidence: 97%